2014
DOI: 10.3892/etm.2014.2075
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the clinicopathological characteristics of large cell carcinoma of the lung

Abstract: The aim of the present study was to analyze and summarize the clinicopathological characteristics of large-cell lung carcinoma (LCLC) of the lung, in order to improve the definite diagnosis rate of LCLC. Clinicopathological data of 174 patients with LCLC, confirmed pathologically, were retrospectively reviewed. The 174 cases of LCLC accounted for 5.7% of the total lung cancer cases during the corresponding time period at the Affiliated Cancer Hospital of Tianjin Medical University (Tianjin, China), among which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…Lung cancer is a disease that severely threatens human health and its incidence shows yearly increases (1). Lung cancer accounts for the highest number of cancer-associated mortalities in women and men worldwide (2).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is a disease that severely threatens human health and its incidence shows yearly increases (1). Lung cancer accounts for the highest number of cancer-associated mortalities in women and men worldwide (2).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoepithelioma-like carcinoma (LELC) is one of the rare histological types of lung cancer, classified into one subtype of large cell carcinoma (LCC) (1), with the incidence of 1.15% to 5.90% of total LCC (2,3). It was reported that LELC was commonly found in the relatively young non-smoking Asian population, without a distinctive difference with respect to gender; more than half the patients were at an early stage (stage I and II) and were treated by complete resection (4).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary LCNEC is biologically aggressive, with poor prognosis (Fasano et al 2015). The 5-year OS rate for LCNEC after resection has been reported to range from 13 to 57% (Liang et al 2015;Varlotto et al 2011;Younossian et al 2002). Similarly, in our study, we found that the 5-year OS rate in the older patient group and the younger group as 13.47% and 20.51%, respectively, which are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%